A socio-cultural explanation of black entrepreneurship in South Africa - M. J. Co (South African Journal of Business Management, 2003)
This article attempts to provide the reader an analysis of why entrepreneurship levels among indigenous Africans are low by specifically using socio-cultural theories. Traditional views of entrepreneurship have emphasised psychological and economic models. Although these views explain entrepreneurial activity, neither can explain it holistically. The sociocultural theoretical approach takes into account differences among societies and cultures in explaining entrepreneurial activity. The choice of this theoretical perspective and the specific theories highlighted is rationalised in the first section of this paper. The paper covers five main socio-cultural theories namely: Webers Protestant ethic, Hagens withdrawal of status, social mobility, marginality and role models. A model is then conceptualised, incorporating the different variables affecting entrepreneurship as identified from the above-mentioned theories and using the Black South Africans as a case illustration.
Keywords: 650